PEMBELAJARAN BERBASIS LINGKUNGAN DALAM PENINGKATAN HASIL BELAJAR PESERTA DIDIK SMPK DON BOSCO ATAMBUA PADA MATERI KLASIFIKASI TUMBUHAN MONOKOTIL DAN DIKOTIL - Berek, Pius A L; Mau, Theresia Adelina Maria (PT. Media Akademik Publisher, 2024)
Outdoor learning is learning through the application of the natural environment as a learning resource that allows students to be able to see, do something, involve themselves in the learning process (undergoing) and experience directly the things being studied. Learning activities will be more meaningful and valuable, because students or students are faced with actual events and situations. Learning is more real, more flexible, and the truth is more accountable. The aim of writing this good practice is to understand the concept of monocot and dicot plant classification after using an environment-based learning method, namely outdoor learning, and to measure whether outdoor learning can improve the learning outcomes of class VII students at Don Bosco Atambua Middle School on the material of monocot and dicot plant classification. The method used in this good practice is the application of outdoor learning to learning. The problem with this good practice is the lack of student learning outcomes in understanding science material, especially biology. The student's score did not reach the KKM set by the school, namely 75. The use of outdoor learning is rarely carried out by biology teachers at SMPK Don Bosco Atambua. Students tend to get bored studying in class. Abstract material concepts and complicated vocabulary regarding the classification of monocot and dicot plants, namely their characteristics. Taproot, fibrous, one and two pieces, parallel veins, pinnate and finger, lack of practical work, low learning motivation and so on. Assessment of student learning outcomes is obtained from evaluation of learning, observations during learning and written interviews with students who are samples in writing this good practice. Analyze data quantitatively and qualitatively by calculating the average student score. The average score obtained by class VII H students before outdoor learning was 55.75, while the score obtained after outdoor learning experienced an increase in learning outcomes with the average score obtained being 95.77 from a total of 34 students. This shows that understanding the material on the classification of monocot and dicot plants using the outdoor learning model is very effective in improving student learning outcomes.